Barley farmland harbors a highly homogeneous soil bacterial community compared to wild ecosystems in the Qinghai-Xizang Plateau - Wang, Xiaolin; Yang, Yibin; Nan, Qiong; Guo, Jian-Wei; Tan, Zhiyuan; Shao, Xiaoming; Tian, Changfu (Frontiers in Microbiology, 2024)
Introduction Understanding patterns and processes of microbial biogeography in soils is important for monitoring ecological responses to human activities, particularly in ecologically vulnerable areas such as the Qinghai-Xizang Plateau. Highland barley is the staple food of local people and has mainly been cultivated along the Yarlung Zangbo River valley in Xizang. Methods Here we investigated soil bacterial communities from 33 sampling sites of highland barley farmland in this region and compared them to those from wild ecosystems including alpine tundra, meadow, forest, and swamp. Additionally, the effects of environmental factors on bacterial communities, as well as the relative importance of stochastic and deterministic processes in shaping the beta diversity of soil bacterial communities in alpine ecosystems were assessed. Results In contrast to soils of wild ecosystems, these farmland samples harbored a highly homogeneous bacterial community without significant correlations with geographic, elevation, and edaphic distances. Discriminant bacterial taxa identified for farmland samples belong to Acidobacteria, with Acidobacteria Gp4 as the dominant clade. Although Acidobacteria were the most abundant members in all ecosystems, characterized bacterial taxa of meadow and forest were members of other phyla such as Proteobacteria and Verrucomicrobia. pH and organic matter were major edaphic attributes shaping these observed patterns across ecosystems. Null model analyses revealed that the deterministic assembly was dominant in bacterial communities in highland barley farmland and tundra soils, whereas stochastic assembly also contributed a large fraction to the assembly of bacterial communities in forest, meadow and swamp soils. Discussion These findings provide an insight into the consequences of human activities and agricultural intensification on taxonomic homogenization of soil bacterial communities in the Qinghai-Xizang Plateau.